Fish Fauna and Fisheries in the Coastal Waters of Similajau, Bintulu, Sarawak, Malaysia - Lee, Nyanti; Jongkar, Grinang; James, Bali; Norhadi, Ismail (Graduate School of Kuroshio Science, Kochi University, 2014)
The coastal waters of Similajau serve as traditional fishing grounds for fishermen from Kuala Nyalau and for those from as far away as Bintulu. This study on fish fauna and fisheries in the area was carried out before the construction of Samalaju Industrial Park and Samalaju Port. It was aimed at documenting fish fauna composition and fisheries in the area so that data collected could provide future baseline information. Subjects for the study were collected using monofilament gill nets of three different mesh sizes and monofilament drift nets. A total 1,336 fish comprising 42 families and 120 species were caught from the area. The five dominant families were Carangidae (17.8%), Engraulidae (16.2%), Pristigasteridae (10.7%), Ariidae (8.3%) and Synodontidae (7.8%). The five dominant species collected were Parastromateus niger (13.1%), Harpodon nehereus (7.6%), Setipinna taty (4.3%), Setipinna tenuifilis (4.2%), and Ilisha elongate (3.9%). Fishing activities were carried out within 10 km of the coastline using a small size fiberglass boat powered by a 15 to 40 hp engine. Fishing methods employed included gill nets, drift nets, hooks and lines, long lines, trap nets, cast nets and push nets. The fishing season is from March to September, when the sea is calmer, and peaks in June and July. The quantity of fish caught ranged from 50 to 200 kg per fishing trip.